Resiliência e apoio social em idosos: uma interface com a qualidade de vida - Roque, Susimauren Navarro (2013)
The elderly are agrowing segment of the population, based on that evidence it is extremely important to identify their physical, functional and social capabilities that have been presented in the routine of this population.The concept of resilience refers to the capabilities of humans to adapt and overcome risk and adversity. This ability causes people to not lose their initial psychosocial functioning.Social support has been defined as a protective factor that occurs as long as the relationships which have developedalong the life influence in overcoming adversities through mechanisms of effective cognitive and emotional control. The quality of life for the elderly means being satisfied with their current life and develops positive expectations about the future. In this context, it was investigated the relationship between resilience, social support and quality of life in a sample of elderly in Cuiabáa city in the state of Mato Grosso, in Brazil. This study counted on a methodology characterized as cross-sectional of quantitative approach. This study relied on a methodology characterized as cross-sectional quantitative approach. The sample consisted on 270 elderly Federal Institute of Mato Grosso - IFMT, Social Centres for the Elderly and Community Restaurant. It was used scales (RSA I; Nadaf, 2013) Social Support SSQ6 (Sarason, Sarason, Shearin e Pierce, 1987), Hospital, Anxiety and Depression Scale (HADS, Zigmond & Snaith, 1983) and Quality of Life WHOQOL-BREF (Fleck et al.2002). The results indicated that the older participants (over 75 years) (M=161.30,SD = 24.13) and the women (M=157.01, SD = 26.90) presented higher scores on resilience, confirming the hypotheses I and II. It was observed a significant positive association between resilience and subjective social support(r =.20, p<.001), resilience and quality of life (r = .23, p<.05)and social support and quality of life (r = .12, p<.05) at the studied sample, confirming hypotheses IIIa, IVa and Va. It was also observed that the elderly who scored higher on social support presented higher scores in quality of life (M=97,19 and DP=8,18)and theelderly who presented higher resilience presented higher scores in social support (p<.001) and quality of life (p<.001), confirming the hypothesis IIIb, IVb and Vb. Based on these results it isassumed that the consequential losses of aging might be compensated through the protective factors such as resilience and social support, promoting better conditions and also better quality of life for the elderly.